ADVANTAGES AND DISADVANTAGES OF USING HYBRID VEHICLES - Mukimova Davlatkhan Karimovna (TADQIQOTLAR, 2025)
Abstract. The article describes the advantages and disadvantages of using hybrid vehicles, and also highlights that urban vehicles that travel long distances during their lifetime (taxis are a typical example), vehicles that are less commonly used or mainly operate outside cities, of course, hybrid technology can be useful.